Fresh-look effect of audit firm and audit partner rotations? Evidence from European key audit matters - Florian Philipp Federsel (International Journal of Auditing, 2024)
Many countries worldwide mandate the rotation of audit partners or audit firms to reinforce independence and professional skepticism. The European Union is a rare instance requiring audit firm and audit partner rotation simultaneously. By analysing 6,103 firm-year observations of non-financial firms from 29 European countries between 2018 and 2022, this study finds that audit firm rotations are associated with considerable changes in key audit matters, suggesting the existence of a fresh-look effect. In contrast, audit partner rotations appear to induce only limited variations in the key audit areas. Additional analyses reveal that the results are consistent across mandatory and voluntary rotations. Collectively, the findings suggest that audit firm rotations enable auditors to overcome institutional pressures toward standardisation within audit firms, while practical considerations such as the requirement of gradual rotation mechanisms within audit firms might limit individual audit partners' influence. This study adds to the inconclusive literature on the effects of (mandatory) audit partner and audit firm rotations. Further, the results contribute new insights into the consequences of the EU audit reform that has introduced mandatory audit firm rotation and provide evidence in favour of audit firm rotation requirements for other regulators.
Keywords: 650; audit firm rotation; audit partner rotation; auditor change; auditor switch; fresh look; key audit matters